2008
DOI: 10.1016/j.jvs.2008.04.041
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of the outcome after small saphenous varicose vein surgery with one-year follow-up

Abstract: Stripping of the SSV significantly reduced the rate of SPJ incompetence after one year without increasing the rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 21 publications
3
40
1
1
Order By: Relevance
“…In one recent prospective multicentre observational study paraesthesia was present in 27 per cent of legs at 6 weeks, and in the majority this persisted after 12 months 3 . Two studies reported visible recurrent varicose veins in 26 and 30 per cent of patients at 1 and 5 years respectively 3,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one recent prospective multicentre observational study paraesthesia was present in 27 per cent of legs at 6 weeks, and in the majority this persisted after 12 months 3 . Two studies reported visible recurrent varicose veins in 26 and 30 per cent of patients at 1 and 5 years respectively 3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the literature indicates that outcomes after surgery for SSV are often suboptimal, with high rates of recurrence and a significant complication rate 2 -9 . Popliteal fossa anatomy is highly variable and, despite preoperative duplex marking, surgery is often technically inadequate, with an intact SPJ being reported in 24-47 per cent of patients at 6 weeks 3,5,8 . In one recent prospective multicentre observational study paraesthesia was present in 27 per cent of legs at 6 weeks, and in the majority this persisted after 12 months 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that femoral and popliteal vein incompetency regresses after the management of saphenous incompetency, 4,12,13,[22][23][24] the fate of an incompetent GCV is unknown. 12) In the early three cases and the great saphenous vein case, the incompetency of the GCV did not improve after saphenous vein surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, sural nerve injury is still considered a major and potentially underreported complication [25, 26]. Due to the fact that no heat and tumescent is used in MOCA™, nerve injury after SSV ablation might become a redundant complication.…”
Section: Discussionmentioning
confidence: 99%